2000
DOI: 10.1034/j.1600-0765.2000.035004186.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of areca nut extracts on the functions of human neutrophils in vitro

Abstract: Aqueous extracts of ripe areca nut without husk (ripe ANE) and fresh and tender areca nut with husk (tender ANE) were examined for their effects on the defensive functions of human neutrophils. Exposure of peripheral blood neutrophils to ripe ANE and tender ANE inhibited their bactericidal activity against oral pathogens, including Actinobacillus actinomycetemcomitans and Streptococcus mutans, in a dose-dependent manner. At the concentrations tested, ripe and tender ANEs did not significantly affect the viabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 24 publications
5
57
0
Order By: Relevance
“…In both the groups, the phagocytic activity of neutrophils was reduced when they were treated with rANE as compared to tANE. This was consistent with the findings of another study which was done by Hung Sl et al, where they compared the neutrophil function which was obtained from peripheral blood which was treated with various concentrations of tANE, rANE, arecoline and catechin [12]. Another study showed that both rANE and tANE inhibited the phagocytic activity of neutrophils in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…In both the groups, the phagocytic activity of neutrophils was reduced when they were treated with rANE as compared to tANE. This was consistent with the findings of another study which was done by Hung Sl et al, where they compared the neutrophil function which was obtained from peripheral blood which was treated with various concentrations of tANE, rANE, arecoline and catechin [12]. Another study showed that both rANE and tANE inhibited the phagocytic activity of neutrophils in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 79%
“…they produce toxins and other factors which either reduce neutrophil function or kill neutrophils [4]. However, it has been seen that the leukotoxicity of different strains of A.actinomycetemcomitans was not the main determinant that modified its interaction with human neutrophils, since phagocytosis and killing of the leukotoxic strains of A.actinomycetemcomitans could occur before the leukotoxin destroyed the neutrophils [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations